Relationship for The Establishment of Local Regulations in The Job Creation Law - Watoni Noerdin (Fakultas Hukum Universitas Lampung, 2022)
The job creation law was created to open Indonesia's widest possible investment climate. But so far, investors still face obstacles on investment in the form of complex regulations. This can be seen from the disharmony and lack of coordination between regional and central government regulations. In that regard, how is the relationship between establishing local regulations in job creation law? The method used in this research is normative legal research with a qualitative approach method with a focus on regulations and related data to answer problems. It can be concluded that Article 174 of the Job Creation law adds rules regarding the relationship between the central and local governments, namely the authority of local governments as part of the presidential authority. Article 176 a quo also changes several local government authorities. For example, the licensing authority in Article 350 of Law Number 23 of 2014. Under Government regulations Number 6 of 2021, Article 3 regarding the Implementation of Business Licensing in the Regions states that such act is carried out by the Central Government, Provincial Government, and City/Regency Government following their respective authorities based on the provisions of laws and regulations. From the licensing rules perspective, it is not executive preview as a form of preventive supervision but top-down control that dominates. This can potentially eliminate local content and conditions based on regional interests.